A method for manufacturing and verifying a solid-state battery

By alternating the composite technology of oxides and polymer solid electrolyte materials, the problem of poor stability and low lithium -ion transmission performance of solid battery interface is solved, and the electrochemical performance improvement and security enhancement are achieved.

CN115133131BActive Publication Date: 2025-01-28SHUANGDENG GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210717634.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-23
Publication Date
2025-01-28
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

The solid-solid interface stability of solid-state batteries is poor, affecting the electrochemical performance and cycle life, and the transmission performance of lithium ions is lower than that of liquid lithium batteries.

Method used

The composite technology of alternating oxides and polymer solid electrolyte materials to form a composite solid -state electrolyte material, reduce the interface resistance, and enhance the mechanical strength through UV aggregation.

Benefits of technology

Effectively improve the stability of the interface, improve the electrochemical performance of solid -state batteries, extend the cycle life, and improve the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115133131B_ABST
    Figure CN115133131B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of solid-state batteries, and in particular to a method for manufacturing a solid-state battery, the steps of which are as follows: S1. forming a first layer of solid electrolyte membrane; S2. forming a composite solid electrolyte membrane; S3. forming a composite solid electrolyte layer; S4. preparing a solid-state battery; The present invention provides a method for manufacturing a solid-state battery with improved interface stability and electrochemical performance and a verification method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for manufacturing and verifying a solid-state battery. Background Art

[0002] Solid-state batteries are a type of battery technology that uses solid electrodes and solid electrolytes compared to today's lithium-ion batteries and lithium-ion polymer batteries. Among them, solid electrolytes are the core components of solid-state batteries, which are mainly divided into polymer solid electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. Since the content of liquid electrolytes in solid-state batteries is reduced, or liquid electrolytes are not used at all, the safety performance of lithium-ion batteries has been greatly improved. Therefore, in recent years, solid-state batteries have become a research hotspot in the lithium battery industry, and have attracted the attention of major scientific research institutes, car companies, and battery companies.

[0003] Although solid-state batteries are highly safe, the solid-solid interface stability between the solid electrolyte and the electrode is slightly worse than that of liquid lithium batteries, which will affect the electrochemical performance of solid-state batteries and reduce their cycle life. In addition, the transmission performance of lithium ions in solid-state batteries is lower than that of liquid lithium batteries due to the use of solid electrolyte materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and shortcomings of the prior art and to provide a method for manufacturing and verifying a solid-state battery with improved interface stability and electrochemical performance.

[0005] The technical solution to achieve the purpose of the present invention is: a method for manufacturing a solid-state battery, the steps are as follows:

[0006] S1. Formation of the first solid electrolyte membrane: mixing the first solid electrolyte material with a lithium salt, a surfactant and a solvent, casting the mixture on a polytetrafluoroethylene surface, and drying the mixture;

[0007] S2. Formation of a composite solid electrolyte membrane: After the second solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to a partial area on the surface of the first solid electrolyte membrane and subjected to UV polymerization;

[0008] S3. Formation of a composite solid electrolyte layer: After the third solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to the remaining area of ​​the composite solid electrolyte membrane surface that is not filled with the second solid electrolyte material, and UV polymerization is performed;

[0009] S4. Preparation of a solid-state battery: assembling a composite solid electrolyte layer between the positive electrode and the negative electrode;

[0010] The filling area of ​​the second solid electrolyte material and the third solid electrolyte material divides the surface of the first solid electrolyte membrane into equal parts;

[0011] The second solid electrolyte material and the third solid electrolyte material are coated alternately, and the total coating amount of the second solid electrolyte material and the third solid electrolyte material is equal;

[0012] The first solid electrolyte material is an oxide;

[0013] The second solid electrolyte material and the third solid electrolyte material are polymers, and the coating thicknesses of the second solid electrolyte material and the third solid electrolyte material are equal.

[0014] Furthermore, the equal parts are divided into two equal parts, four equal parts or eight equal parts.

[0015] A solid-state battery verification method, the steps are as follows:

[0016] S1. AC impedance test: Perform an AC impedance test on the solid-state battery prepared by the above-mentioned preparation method to record the interface and SEI film conditions;

[0017] S2. Heating test: Perform a heating test on the solid-state battery after step S1 to observe whether the solid-state battery catches fire under different temperature and time test parameters, and record the limit conditions;

[0018] S3. AC impedance test: Perform an AC impedance test on the solid-state battery after step S2 to record the interface and SEI film conditions;

[0019] S4. Scanning electron microscope test: disassemble the solid-state battery after step S3, and perform scanning electron microscope test on the positive electrode sheet, the negative electrode sheet and the composite solid electrolyte layer respectively;

[0020] S5. Solid-state battery optimization: Compare and analyze the test results of the heating test, AC impedance test and scanning electron microscope test, adjust the production parameters of the solid-state battery based on the analysis results, and then use the above-mentioned production method to produce a solid-state battery according to the adjusted production parameters, and perform heating test, AC impedance test and scanning electron microscope test on the solid-state battery until the safety of the solid-state battery is improved.

[0021] Furthermore, the solid-state battery obtained in step S5 is subjected to an electrochemical performance test.

[0022] Furthermore, the initial test parameters of the heating test are temperature: 130° C., time: 30 min.

[0023] Furthermore, the adjustment rule of the test parameters in the heating test is: the temperature is increased by 10°C / time, and the time is extended by 30min / time.

[0024] After adopting the above technical solution, the present invention has the following positive effects:

[0025] (1) The present invention alternately coats two different solid electrolyte materials on different areas on the surface of the solid electrolyte membrane to form a composite solid electrolyte material, which gives full play to the high ionic conductivity of the oxide solid electrolyte material and the high mechanical strength of the polymer solid electrolyte material, can effectively reduce the interface resistance, and cope with the volume change of the electrode material, so that the electrode material and the solid electrolyte can be closely combined, thereby effectively improving the interface stability and improving the electrochemical performance of the solid-state battery;

[0026] (2) The present invention coats the positive electrode slurry on the surface of the solid electrolyte, which enables the positive electrode to be in close contact with the solid electrolyte, facilitating the transmission of lithium ions between the positive electrode and the solid electrolyte;

[0027] (3) The present invention compares and analyzes the microscopic morphology, interface performance and SEI film performance of solid-state batteries before and after heating tests, analyzes the performance rules of solid-state batteries under different manufacturing parameters, optimizes battery design, and combines electrochemical performance tests to ultimately obtain a highly safe solid-state battery;

[0028] (4) The present invention combines the advantages of oxide solid electrolytes and polymer solid electrolytes and eliminates the diaphragm. The first layer of solid electrolyte membrane takes on the role of diaphragm, thereby effectively avoiding internal short circuits caused by high-temperature shrinkage of the diaphragm, which is beneficial to further improve the safety of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to make the content of the present invention easier and clearer to understand, the present invention is further described in detail below based on specific embodiments and in conjunction with the accompanying drawings, wherein:

[0030] Figure 1 A flow chart of a method for manufacturing a solid-state battery of the present invention;

[0031] Figure 2 The present invention is a flow chart of the solid-state battery verification method. DETAILED DESCRIPTION

[0032] Example 1

[0033] like Figure 1 As shown, a method for making a solid-state battery, the steps are as follows:

[0034] S1. Formation of the first solid electrolyte membrane: mixing the first solid electrolyte material with a lithium salt, a surfactant and a solvent, casting the mixture on a polytetrafluoroethylene surface, and drying the mixture;

[0035] S2. Formation of a composite solid electrolyte membrane: After the second solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to a partial area on the surface of the first solid electrolyte membrane and subjected to UV polymerization;

[0036] S3. Formation of a composite solid electrolyte layer: After the third solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to the remaining area of ​​the composite solid electrolyte membrane surface that is not filled with the second solid electrolyte material, and UV polymerization is performed;

[0037] S4. Preparation of solid-state battery: assemble the composite solid electrolyte layer between the positive electrode and the negative electrode.

[0038] This production method alternately coats two different solid electrolyte materials on different areas of the surface of the solid electrolyte membrane to form a composite solid electrolyte material, giving full play to the high ionic conductivity of the oxide solid electrolyte material and the high mechanical strength of the polymer solid electrolyte material, which can effectively reduce the interface resistance, and respond to the volume change of the electrode material, so that the electrode material and the solid electrolyte can be closely combined, thereby effectively improving the interface stability and improving the electrochemical performance of the solid-state battery. In this production method, the second solid electrolyte material is first filled, and then the third solid electrolyte material is filled after UV polymerization, so as to avoid the mutual flow of the two solid electrolyte materials during polymerization, resulting in the formation of cross-linked polymers in the mutually infiltrated parts, so that the infiltrated parts are different in composition from other parts, affecting the performance of the solid-state battery. In addition, this production method combines the advantages of oxide solid electrolytes and polymer solid electrolytes, and cancels the diaphragm, and the first layer of solid electrolyte membrane assumes the role of the diaphragm, thereby effectively avoiding the internal short circuit caused by the high-temperature shrinkage of the diaphragm, which is conducive to further improving the safety of the solid-state battery.

[0039] In the above steps S2 and S3, the coating area of ​​the second solid electrolyte material and the third solid electrolyte material divides the surface of the first layer of solid electrolyte membrane into equal parts. Specifically, the coating area is divided into two equal parts, four equal parts or eight equal parts. Of course, according to the analysis of the test results, the number of equal parts can be increased proportionally. The second solid electrolyte material and the third solid electrolyte material are coated at intervals, and the total coating amount of the second solid electrolyte material and the third solid electrolyte material is equal. The first solid electrolyte material is an oxide, and the second solid electrolyte material and the third solid electrolyte material are polymers, wherein the second solid electrolyte material and the third solid electrolyte material are respectively formed by UV polymerization of monomer materials, and the coating thickness is equal.

[0040] The specific steps of the above step S4 are as follows:

[0041] S41. Preparing a ternary or lithium iron phosphate cathode slurry, coating it on the surface of the first solid electrolyte membrane away from the composite solid electrolyte layer, and drying to obtain a cathode / composite solid electrolyte layer;

[0042] S42. Assemble the positive electrode / composite solid electrolyte layer and the negative electrode to produce a solid-state battery.

[0043] The present invention coats the positive electrode slurry on the surface of the first layer of solid electrolyte membrane, which enables the positive electrode to be in close contact with the solid electrolyte, and is beneficial to the transmission of lithium ions between the positive electrode and the solid electrolyte.

[0044] Example 2

[0045] A method for manufacturing a solid-state battery, the steps are as follows:

[0046] S1. Take the LAGP solid electrolyte material and mix it evenly with the lithium salt, surfactant and solvent, cast it on the surface of polytetrafluoroethylene, and form the first layer of solid electrolyte membrane after drying;

[0047] S2. After mixing the PEGDA solid electrolyte material with the lithium salt, the solvent and the initiator, the mixture is applied to the upper area of ​​the LAGP solid electrolyte membrane surface divided into two equal parts, and UV polymerization is performed to form a composite solid electrolyte membrane;

[0048] S3. After VC solid electrolyte material is mixed with lithium salt, solvent and initiator, it is applied to the lower area of ​​the composite solid electrolyte membrane surface divided into two equal parts, that is, the area not filled with PEGDA solid electrolyte material, and UV polymerization is performed to form a composite solid electrolyte layer;

[0049] S4. Assemble the composite solid electrolyte layer between the positive electrode and the negative electrode to obtain a solid-state battery.

[0050] Example 3

[0051] A method for manufacturing a solid-state battery, the steps are as follows:

[0052] S1. Take the LAGP solid electrolyte material and mix it evenly with the lithium salt, surfactant and solvent, cast it on the surface of polytetrafluoroethylene, and form the first layer of solid electrolyte membrane after drying;

[0053] S2. After mixing the PEGDA solid electrolyte material with the lithium salt, solvent and initiator, the mixture is applied to the upper left and lower right areas of the four-divided LAGP solid electrolyte membrane surface, and UV polymerization is performed to form a composite solid electrolyte membrane;

[0054] S3. After mixing VC solid electrolyte material with lithium salt, solvent and initiator, fill and coat the lower left and upper right areas of the composite solid electrolyte membrane surface in four equal parts, and perform UV polymerization to form a composite solid electrolyte layer;

[0055] S4. Assemble the composite solid electrolyte layer between the positive electrode and the negative electrode to obtain a solid-state battery.

[0056] Example 4

[0057] A method for manufacturing a solid-state battery, the steps are as follows:

[0058] S1. Take LATP solid electrolyte material and mix it evenly with lithium salt, surfactant and solvent, cast it on the surface of polytetrafluoroethylene, and form the first layer of solid electrolyte membrane after drying;

[0059] S2. After mixing the ETPTA solid electrolyte material with a lithium salt, a solvent and an initiator, the mixture is applied to the upper area of ​​the LAGP solid electrolyte membrane surface divided into two equal parts, and UV polymerization is performed to form a composite solid electrolyte membrane;

[0060] S3. After VC solid electrolyte material is mixed with lithium salt, solvent and initiator, it is applied to the lower part of the surface of the composite solid electrolyte membrane, which is not filled with ETPTA solid electrolyte material, and UV polymerization is performed to form a composite solid electrolyte layer;

[0061] S4. Assemble the composite solid electrolyte layer between the positive electrode and the negative electrode to obtain a solid-state battery.

[0062] Example 5

[0063] like Figure 2 As shown, a solid-state battery verification method comprises the following steps:

[0064] S1. AC impedance test: Perform AC impedance test on solid-state batteries to record the interface and SEI film conditions;

[0065] S2. Heating test: Perform a heating test on the solid-state battery after step S1 to observe whether the solid-state battery catches fire under different temperature and time parameters, and record the limit conditions;

[0066] S3. AC impedance test: Perform an AC impedance test on the solid-state battery after step S2 to record the interface and SEI film conditions;

[0067] S4. Scanning electron microscope test: disassemble the solid-state battery after step S3, and perform scanning electron microscope test on the positive electrode sheet, the negative electrode sheet and the composite solid electrolyte layer respectively;

[0068] S5. Solid-state battery optimization: Compare and analyze the test structures of the heating test, AC impedance test, and SEM test, adjust the solid-state battery manufacturing parameters (such as the number of equal parts) based on the analysis results, and then manufacture the solid-state battery according to the adjusted manufacturing parameters, and conduct heating tests, AC impedance tests, and SEM tests on the solid-state battery until the safety of the solid-state battery is improved.

[0069] Four groups of solid-state batteries with the best safety performance are selected from the solid-state batteries obtained in step S5 for electrochemical performance testing, and the solid-state batteries with high safety and good electrochemical performance are obtained by combining the rate and cycle test results.

[0070] When conducting the heating test, the initial test parameters were set to temperature: 130°C, time: 30 min. Two groups of solid-state batteries were prepared, and the two groups of solid-state batteries were subjected to the same heating test, but the test time was not synchronized. When the first group did not catch fire, the second group was subjected to the same test, and the control variable method was used to increase the test parameters, with the temperature increasing by 10°C / time and the time extending by 30 min / time, until the first group of solid-state batteries caught fire. At this time, the second group of solid-state batteries was not subjected to the same test, and the test parameters before the fire were recorded as the extreme conditions.

[0071] This verification method compares and analyzes the microscopic morphology, interface performance and SEI film performance of solid-state batteries before and after heating tests, analyzes the performance rules of solid-state batteries under different manufacturing parameters, optimizes battery design, and combines electrochemical performance tests to ultimately obtain highly safe solid-state batteries. In addition, this verification method can effectively verify the safety of solid-state batteries and quickly optimize battery design.

[0072] Example 6

[0073] A method for manufacturing and verifying a solid-state battery, the steps are as follows:

[0074] S1. Formation of the first solid electrolyte membrane: mixing the first solid electrolyte material with a lithium salt, a surfactant and a solvent, casting the mixture on a polytetrafluoroethylene surface, and drying the mixture;

[0075] S2. Formation of a composite solid electrolyte membrane: After the second solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to a partial area on the surface of the first solid electrolyte membrane and subjected to UV polymerization;

[0076] S3. Formation of a composite solid electrolyte layer: After the third solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to the remaining area of ​​the composite solid electrolyte membrane surface that is not filled with the second solid electrolyte material, and UV polymerization is performed;

[0077] S4. Preparation of solid-state battery: assemble the composite solid electrolyte layer between the positive electrode and the negative electrode.

[0078] S5. AC impedance test: Perform an AC impedance test on the solid-state battery prepared in step S4 to record the interface and SEI film conditions;

[0079] S6. Heating test: Perform a heating test on the solid-state battery after step S5 to observe whether the solid-state battery catches fire under different temperature and time parameters, and record the limit conditions;

[0080] S7. AC impedance test: Perform an AC impedance test again on the solid-state battery after step S6 to record the interface and SEI film conditions;

[0081] S8. Scanning electron microscope test: disassemble the solid-state battery after step S7, and perform scanning electron microscope test on the positive electrode sheet, the negative electrode sheet and the composite solid electrolyte layer respectively;

[0082] S9. Solid-state battery optimization: Compare and analyze the test structures of the heating test, the AC impedance test, and the SEM test, adjust the manufacturing parameters of the solid-state battery according to the analysis results, and then return to step S1 according to the adjusted manufacturing parameters until the safety of the solid-state battery is improved;

[0083] S10. Electrochemical performance test: In step S9, four groups of solid-state batteries with the best safety performance are selected for electrochemical performance test. Combined with the rate and cycle test results, a solid-state battery with high safety and good electrochemical performance is obtained.

[0084] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for manufacturing a solid-state battery, characterized in that: Here are the steps: S1. Formation of the first solid electrolyte membrane: mixing the first solid electrolyte material with a lithium salt, a surfactant and a solvent, casting the mixture on a polytetrafluoroethylene surface, and drying the mixture; S2. Formation of a composite solid electrolyte membrane: After the second solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to a partial area on the surface of the first solid electrolyte membrane and subjected to UV polymerization; S3. Formation of a composite solid electrolyte layer: After the third solid electrolyte material is mixed with a lithium salt, a solvent, and an initiator, it is applied to the remaining area of ​​the composite solid electrolyte membrane surface that is not filled with the second solid electrolyte material, and UV polymerization is performed; S4. Preparation of a solid-state battery: assembling a composite solid electrolyte layer between the positive electrode and the negative electrode; The coating area of ​​the second solid electrolyte material and the third solid electrolyte material divides the surface of the first solid electrolyte membrane into equal parts; The second solid electrolyte material and the third solid electrolyte material are coated alternately, and the total coating amount of the second solid electrolyte material and the third solid electrolyte material is equal; The first solid electrolyte material is an oxide; The second solid electrolyte material and the third solid electrolyte material are polymers, and the coating thicknesses of the second solid electrolyte material and the third solid electrolyte material are equal.

2. The method for manufacturing a solid-state battery according to claim 1, characterized in that: The division is into two equal parts, four equal parts or eight equal parts.

3. A solid-state battery verification method, characterized in that: The steps are as follows, S1. AC impedance test: performing an AC impedance test on a solid-state battery prepared by the method of claim 1 or 2, and recording the interface and SEI film conditions; S2. Heating test: Perform a heating test on the solid-state battery after step S1 to observe whether the solid-state battery catches fire under different temperature and time test parameters, and record the limit conditions; S3. AC impedance test: Perform an AC impedance test on the solid-state battery after step S2 to record the interface and SEI film conditions; S4. Scanning electron microscope test: disassemble the solid-state battery after step S3, and perform scanning electron microscope test on the positive electrode sheet, the negative electrode sheet and the composite solid electrolyte layer respectively; S5. Solid-state battery optimization: Compare and analyze the test results of the heating test, AC impedance test and scanning electron microscope test, adjust the production parameters of the solid-state battery according to the analysis results, and then use the production method described in claim 1 or 2 to produce a solid-state battery according to the adjusted production parameters, and perform a heating test, AC impedance test and scanning electron microscope test on the solid-state battery until the safety of the solid-state battery is improved.

4. A solid-state battery verification method according to claim 3, characterized in that: The solid-state battery obtained in step S5 is subjected to electrochemical performance testing.

5. A solid-state battery verification method according to claim 3, characterized in that: The initial test parameters of the heating test are temperature: 130° C., time: 30 min.

6. A solid-state battery verification method according to claim 5, characterized in that: The adjustment rule of the test parameters in the heating test is: the temperature is increased by 10°C / time, and the time is extended by 30min / time.

Citation Information

Patent Citations

  • Solid-state hybrid electrolytes, methods of making same, and uses thereof

    WO2018183771A1

  • Solid electrolyte composite and all-solid-state battery electrode comprising same

    WO2020214009A1